STRATEGI BIMBINGAN DAN KONSELING UNTUK MENGATASI MASALAH AKADEMIK SISWA - Azriyatujjanah Azriyatujjanah; Dini Ayunirmala; Desty Endrawati Subroto (CV. Denasya Smart Publisher, 2025)
In today's global era, interest in learning has shown a significant decline as many individuals are more focused on social media platforms. Social media is not only popular at the local level but has also become an essential element worldwide in supporting daily activities. Although technological advancements have made long-distance communication with loved ones easier, children today tend to use electronic devices more for completing school assignments than for truly understanding the learning materials. They often perceive learning activities as uninteresting, even though without the learning process, one cannot gain extensive knowledge. The decline in learning interest has become more apparent due to technological advancements that provide fast access to information, making people feel less inclined to read or understand step-by-step processes. As a result, many have abandoned traditional learning methods and prefer to use technology as an educational tool rather than reading books. When someone chooses to read, the materials they select are usually not textbooks but rather novels or other works of fiction that are more engaging and entertaining, as they offer various emotional experiences such as joy, sorrow, and pain. This contrasts with textbooks, which are often perceived as boring and less appealing, leading to a reluctance to read them. Consequently, many individuals prefer using technology to solve problems, as it is considered more practical than reading books.